Didactic conditions for the organization of self-study and self-assessment of students in the study of biology - Yerbol Kainarbayev; Ainur Baikenzheeva; Imelda Kemeza; Anar Tazhmakhanova (STAI Miftahul Ula Nganjuk, 2024)
Organizing self-study is essential during the COVID-19 pandemic. Many teachers and students are faced with the problems of remote learning of educational material. Therefore, it is advisable to create and highlight those methods that will facilitate the study of biology. The purpose of this research was to develop approaches, in which students are motivated for self-study and self-assessment with minimal teacher guidance. Schools were selected randomly for the study. Each of them had 4 cohorts per course. In such a cohort, three experimental groups and one control group were randomly selected. One experimental group was given both success criteria and a checklist, another experimental group was given success criteria, and a third experimental group was given a checklist. As a result of the research, it can be seen that the method of teaching the material, as well as the means, affect the success criteria. The use of different methods of self-assessment in the learning process increases the knowledge and motivation of students to study biology. For example, after testing, the students were allowed to independently check their work and analyze their mistakes, or use different colors to highlight those tasks that the student wrote himself (the answer is correct), those with errors and those, with which difficulties arose. In addition, one can improve their communication skills and bonding with their classmates by helping others check their work. The findings will help teachers and other educators meet the educational challenges of the twenty-first century.